An adult case of atypical familial Mediterranean fever (pyrin‐associated autoinflammatory disease) similar to adult‐onset Still's disease. Issue 4 (12th March 2019) - Tsuruma, Hayato; Sato, Hiroe; Hasegawa, Eriko; Nozawa, Yukiko; Nakatsue, Takeshi; Wada, Yoko; Kuroda, Takeshi; Suzuki, Yoshiki; Nakano, Masaaki; Narita, Ichiei
Key Clinical Message: We present a 55‐year‐old woman with periodic fever and symptoms similar to adult‐onset Still's disease (AOSD). She had a heterogeneous mutation of the MEFV gene and colchicine was effective. Atypical familial Mediterranean fever (pyrin‐associated autoinflammatory disease) should be considered in patients with periodic fever accompanied by symptoms similar to AOSD. Abstract : We present a 55‐year‐old woman with periodic fever and symptoms similar to adult‐onset Still's disease (AOSD). She had a heterogeneous mutation of the MEFV gene and colchicine was effective. Atypical familial Mediterranean fever (pyrin‐associated autoinflammatory disease) should be considered in patients with periodic fever accompanied by symptoms similar to AOSD.